The initial fiscal policy response to Covid-19 in Malaysia: The impact of government spending on healthcare sector using dynamic panel data system GMM estimation analysis - Intan Maizura, Abd Rashid; Wan Ahmad Fauzi, Wan Husain; Irza Hanie, Abu Samah; Suraiya, Ibrahim; Hariri, Hamzah; Mohammad Harith, Amlus (AIP Publishing, 2023)
The purpose of this study is to examine empirically the effect of government spending on healthcare systems on malaysia’s economic growth during the early stages of the Covid 19 epidemic. Even as society became aware of the potential dangers of Covid 19, there has been a massive effort to rapidly increase capacity in the healthcare system. In Malaysia, in addition to emphasising the importance of strict adherence to the Movement Control Order (MCO), the government announced an immediate increase in funding for healthcare services as part of the initial phase fiscal policy reply to the Covid 19 outbreak. This study employed Dynamic Panel Data, also identified as a longitudinal study, and collected data over a four-month period, from December 2019 to March 2020, in five Asian countries involved with Covid 19. This study discovered that the Dynamic Panel Data System GMM Estimation model is suitable for interpreting the results, indicating that government expenditure on Covid-19 (p-value = 0.036), unemployment rate and inflation rate have a significant relationship with healthcare sector growth of 1%, 2%, and 5%, respectively. In terms of limitations, such a study only focuses on four months of data from selected Asia countries participating in Covid-19. The findings of panel causality recommend that there are bidirectional links between healthcare sector growth and government spending. Empirical findings suggest that fiscal policy reforms are required to channel healthcare industry growth to increased government spending as a result of Malaysia’s fiscal policy.